Economic evaluation of Danhong injection for the treatment of chronic stable angina in China: A cost-effectiveness analysis - Pengli Su; Kai Zhi; Jing Xiao; Huanhuan Xu; Jun Liu; Zhong Wang; Yanan Yu; Haixia Dang (Science of Traditional Chinese Medicine)
Abstract. Objective. Danhong injection (DHI) is commonly used in China to treat chronic stable angina (CSA), demonstrating significant clinical efficacy and safety. The present study aimed to estimate the cost-effectiveness of DHI combined with standard treatment (ST) compared with ST alone in patients with CSA. Methods. A Markov model with a 3-month cycle and a 1-year time horizon was used to assess the cost-effectiveness of DHI + ST for CSA. Health outcomes were measured as quality-adjusted life years (QALYs), and societal perspective costs were collected in China. Cost-effectiveness was evaluated using the incremental cost-effectiveness ratio (ICER). Sensitivity analysis was performed to test the robustness of results to parameter uncertainty. Results. Analysis demonstrated DHI + ST provided 0.8190 QALYs at an average cost of $3644.24, while ST yielded 0.7884 QALYs costing $2739.54 over 1 year. The incremental analysis indicated DHI + ST dominance, with an ICER of $29,588.91 per QALY gained compared with ST. One-way sensitivity analysis confirmed the robustness of base case findings, and probabilistic sensitivity analysis suggested a 61.66% probability of DHI + ST being cost-effective over ST at a $37,663.26 per QALY threshold. Conclusion. From a societal perspective in China, DHI + ST appears cost-effective for the treatment of CSA compared with ST alone. These findings support recommending DHI as a clinically valuable and cost-effective option in CSA treatment guidelines.